Pengaruh Persepsi Harga dan Kualitas Produk Terhadap Customer Satisfaction dan Keputusan Pembelian - Suyetno (EKONOMI DAN BISNIS DIGITAL, 2024)
The purpose of this study is that we know the analysis of the effect of price perception. Product quality for CustomerSatisfaction and consumer purchasing choices. The object of this research is Indomaret Yoyakarta. The subjects ofthis research are customers who have shopped at Indomaret. This research is quantitative research. The sample ofthis study is part of the population, namely 100 customers who have shopped at Indomaret Yoyakarta. Where thissample is determined by the Slovin formula. The sampling technique used was simple accidental sampling. Datacollection techniques were carried out using a questionnaire or questionnaire method. The data analysis methodused is a regression method determined by t-experiment and classical assumptions. The data that has been obtainedis processed using SPSS 21. The results of this study indicate that the Price Perception Variable has a significanteffect on customer satisfaction based on the t experiment with a potential of 9.488 with a significance of <0.05resulting in Ho being rejected and Ha accepted. Product quality has a significant effect on customer satisfactionbecause it is based on a t-test of 2,973 with a significance <0.05. This results in Ho being rejected and Ha accepted.The Customer Satisfaction variable has a significant effect on consumer purchasing decisions as evidenced by thet-test with a value of 4.574 with a significance <0.05 which makes Ho rejected and Ha accepted. The priceperception variable has a significant effect on consumer purchasing decisions as evidenced by the t-test of 2.127with a significance <0.05 which resulted in Ho being rejected while Ha was accepted. Product quality has asignificant effect on consumer purchasing decisions as evidenced by the t-test of 3.246 with a significance <0.05which makes Ho rejected while Ha is accepted.